ANALISIS SITUASIONAL PERUSAHAAN PENYEDIA LAYANAN BROADBAND DI ERA BISNIS DIGITAL - Sri Damar Setiawan; Rina Oktaviani; Idqan Fahmi; Setiadi Djohar (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. The growing Information and Communication Technology (ICT) industryleading to the convergence of services. The depletion of industry boundaries causesthe level of competition to be more stringent. The latest competition challenge ofbroadband service providers in the digital business era is from Over The Top (OTT)service providers that provide applications and content. The purpose of this researchis to conduct gap analysis and Structure Conduct Performance (SCP) analysis. Gapanalysis includes the firm's capability gap against environmental turbulenceexpectations as well as resource gaps and performance. The method used isquantitative analysis and descriptive statistics analysis using secondary data. Theresearch results have shown that the company's capability has not been suitable tothe expectations of environmental turbulence and there are gaps in resources andperformance. This research also results have shown that the market concentrationlevel in industry is high, but the behavior of the company competes and producesgood profit level. The implication of the research results are the company needs tomake efforts to transform the capability and strategy to keep the company growingand sustainable.